Optical film and method for manufacturing an optical film
Patent Information
- Application Number
- JP2025030220
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2026-09-08
AI Technical Summary
【0018】 本発明によれば、環境安全性に優れ、透明性が高く、十分な機械強度を有した光学フィルムおよびその光学フィルムの製造法を提供することができる。
Smart Images

Figure 2026142926000001 
Figure 2026142926000002 
Figure 2026142926000003
Abstract
Description
[Technical Field]
[0001] This invention relates to an optical film and a method for manufacturing an optical film. [Background technology]
[0002] Display devices such as liquid crystal displays, organic EL displays, and electronic paper, as well as electronic devices such as solar cells and touch panels, are required to be thinner, lighter, and more flexible. By replacing the glass materials used in these devices with film materials, flexibility, thinning, and weight reduction can be achieved. Transparent polyimide film has been developed as a glass substitute material and is used in display substrates and cover films, etc.
[0003] Studies are underway to improve the bending resistance of transparent polyimide films for use in flexible applications such as flexible displays. For example, Patent Document 1 describes that stretching a transparent polyimide film at 290°C improves its bending resistance. However, this method is prone to discoloration due to heating (increase in yellowness), making it difficult to apply to applications requiring high transparency, such as display cover films.
[0004] One known method for improving the transparency of polyimide is to alloy it with other transparent resins. For example, Patent Document 2 describes that a film with excellent mechanical strength and transparency can be produced by stretching a mixture of polyimide containing a diamine with a perfluoroalkyl group and an acrylic resin.
[0005] On the other hand, in recent years, the environmental persistence of per- and polyfluoroalkyl substances (PFAS) has become a problem. Generally, carbon-fluorine bonds contained in organofluorine compounds have high binding energy, and organofluorine compounds are not easily decomposed in the environment. In particular, organofluorine compounds including a structure in which a trifluoromethyl group is bonded to a carbon atom (-C-CF3) or a structure in which carbon atoms are bonded to both ends of a difluoromethylene group (-C-CF2-C-) have low degradability in the environment, and their effects on the human body have also been pointed out. [Prior Art Document] [Patent Document]
[0006] [Patent Document 1] Japanese Patent No. 6912287 [Patent Document 2] WO2023 / 100806 [Summary of the Invention] [Problem to be Solved by the Invention]
[0007] When a transparent polyimide film is stretched at a high temperature, although mechanical strength is improved, it causes coloring, and it is not easy to achieve both transparency and high mechanical strength with conventional transparent polyimide alone. As a means for improving transparency, there is a method of alloying transparent polyimide containing an organofluorine compound and acrylic resin, but the use of an organofluorine compound having high environmental persistence remains a concern from the viewpoint of environmental safety. In view of these problems, an object of the present invention is to provide an optical film excellent in environmental safety, high in transparency, and having sufficient mechanical strength, and a method for producing the same. [Means for Solving the Problem]
[0008] As a result of intensive studies, the present inventors have found that the above problems can be solved by adopting the following configuration.
[0009] 1). An optical film comprising a polyimide having a structure derived from a diamine and a structure derived from a tetracarboxylic dianhydride, and a transparent resin other than polyimide, The diamine includes CF₃-O-, -(CF₂-O) n -, -O-(CF₂-CF₂-O) n -, wherein the diamine comprises a diamine having one or more structures selected from any of the above, where n is an integer of 1 to 20; the ratio of structures derived from a diamine having a CF₃- group directly bonded to an aromatic ring or a -C(CF₃)₂- group directly bonded to an aromatic ring, relative to the total amount of diamine-derived structures in the polyimide, is less than 0.5 mol%; and the ratio of structures derived from a tetracarboxylic dianhydride having a CF₃- group directly bonded to an aromatic ring or a -C(CF₃)₂- group directly bonded to an aromatic ring, relative to the total amount of tetracarboxylic dianhydride-derived structures, is less than 0.5 mol%, The optical film is characterized in that the in-plane birefringence ΔN of the optical film is less than 0.006, and the number of bending resistance cycles when a repeated bending test is performed at a bending radius of 1.0 mm at a rate of one time per second is 100,000 cycles or more.
[0010] 2). The optical film according to 1), wherein the diamine having one or more structures selected from any of CF₃-O-, -(CF₂-O) n -, -O-(CF₂-CF₂-O) n -, where n is an integer of 1 to 20, is selected from 2,2'-bis(trifluoromethoxy)benzidine, 3,3'-bis(trifluoromethoxy)benzidine, and 2,3'-bis(trifluoromethoxy)benzidine.
[0011] 3). The optical film according to 1) or 2), wherein the transparent resin other than the polyimide is selected from acrylic resins and polyesters.
[0012] 4). The optical film according to any one of 1) to 3), wherein the glass transition temperature is 110°C or higher and lower than 260°C.
[0013] 5). The optical film according to any one of 1) to 4), comprising the polyimide and the transparent resin other than the polyimide at a weight ratio in the range of 2:98 to 98:2.
[0014] 6) An optical film according to any one of items 1) to 5), characterized in that the elastic modulus E1 in the first direction, which has the maximum elastic modulus in the plane, and the elastic modulus E2 in the second direction, which is orthogonal to the first direction in the plane, satisfy 100 × (E1 - E2) / E2 < 5.0, and both the elastic modulus E1 in the first direction and the elastic modulus E2 in the second direction are 3.0 GPa or greater.
[0015] 7) An optical film as described in any one of items 1) to 6), having a total light transmittance of 85% or more, a haze of 10% or less, and a yellowness of 5 or less.
[0016] 8) A method for manufacturing an optical film according to any one of items 1) to 7), characterized by biaxial stretching.
[0017] 9) A method for manufacturing an optical film according to 8), wherein the temperature during stretching is less than 260°C. [Effects of the Invention]
[0018] According to the present invention, it is possible to provide an optical film that is environmentally safe, highly transparent, and has sufficient mechanical strength, as well as a method for producing the optical film. [Modes for carrying out the invention]
[0019] [Optical film] The optical film of the present invention is an optical film comprising a polyimide having a structure derived from a diamine and a structure derived from a tetracarboxylic dianhydride, and a transparent resin other than a polyimide, wherein the diamine is CF3-O-,-(CF2-O) n -, -O-(CF2-CF2-O) nThe polyimide comprises a diamine having one or more structures selected from the following (where n is an integer from 1 to 20), wherein the ratio of structures derived from the diamine having a CF3- group directly attached to an aromatic ring or a -C(CF3)2- group directly attached to an aromatic ring to the total amount of structures derived from the diamine is less than 0.5 mol%, and the ratio of structures derived from the tetracarboxylic dianhydride having a CF3- group directly attached to an aromatic ring or a -C(CF3)2- group directly attached to an aromatic ring to the total amount of structures derived from the tetracarboxylic dianhydride is less than 0.5 mol%, the optical film has an in-plane birefringence ΔN of less than 0.006, and the number of bending resistance cycles when repeatedly bent at a bending radius of 1.0 mm at a speed of 1 time per second is 100,000 or more.
[0020] <Polyimide> Polyimide (hereinafter sometimes simply referred to as "PI") is a polymer having a structural unit represented by general formula (I), and is obtained by dehydrating and cyclizing polyamic acid, which is obtained by addition polymerization of tetracarboxylic dianhydride (hereinafter sometimes simply referred to as "acid dianhydride") and diamine. In other words, polyimide is a polycondensate of tetracarboxylic dianhydride and diamine, and has a structure derived from tetracarboxylic dianhydride (tetracarboxylic dianhydride component) and a structure derived from diamine (diamine component). Polyimide can also be synthesized by decarboxylation condensation of diisocyanate and tetracarboxylic dianhydride.
[0021] [ka]
[0022] In general formula (I), X is a tetravalent organic group and Y is a divalent organic group. X is a tetracarboxylic dianhydride residue, which is an organic group obtained by removing two anhydride carboxyl groups from a tetracarboxylic dianhydride represented by general formula (II) below. Y is a diamine residue, which is an organic group obtained by removing two amino groups from a diamine represented by general formula (III) below. When synthesizing polyimide using diisocyanates, Y is a diisocyanate residue, which is an organic group obtained by removing two isocyanate groups from a diisocyanate compound.
[0023] [ka]
[0024] In other words, polyimide contains structural units represented by the following general formula (IIa) and structural units represented by the following general formula (IIIa), and the tetracarboxylic dianhydride-derived structure (IIa) and the diamine-derived structure (IIIa) form imide bonds, thereby giving rise to the structural unit represented by general formula (I).
[0025] [ka]
[0026] Polyimides may contain, in addition to the imide structural unit represented by general formula (I), amide structural units represented by general formula (IV) below, or structural units containing both amide and imide structures represented by (V). Polyimides containing amide structural units or structural units containing both amide and imide structures in addition to imide structural units are also called polyamideimides.
[0027] [ka]
[0028] In general formulas (IV) and (V), Y and Z are divalent organic groups, and W is a trivalent organic group. Y is a diamine residue, as in general formula (I). Z is a dicarboxylic acid residue, which is an organic group obtained by removing two carboxyl groups from a dicarboxylic acid represented by general formula (VI) below. W is a tricarboxylic acid anhydride residue, which is an organic group obtained by removing an anhydride carboxyl group and a carboxyl group from a tricarboxylic acid anhydride represented by general formula (VII) below. In the synthesis of polyamide-imides, dicarboxylic acid derivatives such as dicarboxylic acid dichlorides, dicarboxylic acid anhydrides, and dicarboxylic acid esters represented by general formula (VI'), and tricarboxylic acid anhydride derivatives such as tricarboxylic acid anhydride chloride represented by general formula (VII') are preferably used instead of dicarboxylic acids and tricarboxylic acid anhydrides.
[0029] [ka]
[0030] The diamine-derived structure represented by the above general formula (IIIa) and the dicarboxylic acid-derived structure represented by the following general formula (VIa) form an amide bond, thereby forming an amide structural unit represented by general formula (IV). The diamine-derived structure represented by general formula (IIIa) and the tricarboxylic acid anhydride-derived structure represented by the following general formula (VIIa) form an imide bond and an amide bond, thereby forming a structural unit containing an amide structure and an imide structure represented by general formula (V). In other words, polyamide-imide includes one or more structures selected from either the dicarboxylic acid-derived structure (VIa) or the tricarboxylic acid anhydride-derived structure (VIIa), a tetracarboxylic dianhydride-derived structure (IIa), and a diamine-derived structure (IIIa).
[0031] [ka]
[0032] Polyamide-imides include, for example, the structure of the following general formula (VIII), in which a diamine-derived structure (VIa) is bonded to both ends of a dicarboxylic acid-derived structure (IIIa).
[0033] [ka]
[0034] In general formula (VIII), Y1 and Y2 are diamine residues, and Z1 is a dicarboxylic acid residue. In general formula (IX), Y3 and Y4 are diamine residues, and Z2 is a tricarboxylic acid anhydride residue. If we consider the portion [-Y1-NH-CO-Z1-CO-NH-Y2-] in general formula (VIII) and the portion [-Y3-N-(CO)2-Z2-CO-NH-Y4-] in general formula (IX) as a single divalent organic group, this divalent organic group can be considered as a diamine residue Y containing two amide bonds. That is, a polyimide in general formula (I) that contains an amide bond in the diamine residue Y is a polyamide-imide, and polyamide-imide is a type of polyimide. Hereafter, unless otherwise specified, the term "polyimide" includes "polyamide-imide".
[0035] As mentioned above, polyimide contains structures derived from diamines (diamine component) and structures derived from tetracarboxylic dianhydrides (tetracarboxylic dianhydride component). The polyimide resin used in this embodiment has diamines that are CF3-O-,-(CF2-O) n -, -O-(CF2-CF2-O) n The polyimide comprises a diamine having one or more structures selected from the following (where n is an integer from 1 to 20), wherein the ratio of structures derived from the diamine having a CF3- group directly attached to an aromatic ring or a -C(CF3)2- group directly attached to an aromatic ring to the total amount of structures derived from the diamine is less than 0.5 mol%, and the ratio of structures derived from the tetracarboxylic dianhydride having a CF3- group directly attached to an aromatic ring or a -C(CF3)2- group directly attached to an aromatic ring to the total amount of structures derived from the tetracarboxylic dianhydride is less than 0.5 mol%.
[0036] <Diamine> The diamine used in the polyimide resin of the present invention includes diamine having one or more structures selected from any of CF3-O-, -(CF2-O) n -, -O-(CF2-CF2-O) n -, wherein n is an integer from 1 to 20. Hereinafter, these diamines are referred to as "specific diamines".
[0037] A structure in which the carbon atom of a trifluoromethyl group (-CF3) or the carbon atom of a difluoromethylene group (-CF2-) is bonded to an oxygen atom tends to have higher degradability and lower environmental persistence than a structure in which a trifluoromethyl group is bonded to a carbon atom (-C-CF3) or a structure in which carbon atoms are bonded to both ends of a difluoromethylene group (-C-CF2-C-). Therefore, a polyimide containing a specific diamine as a diamine component has excellent environmental safety compared to conventional soluble polyimides containing an organic fluorine compound such as fluoroalkyl-substituted benzidine as a diamine component.
[0038] Among specific diamines, since they do not fall under the "specific fluorine structure" described later, those having CF3-O- or -(CF2-O) n - are preferred. From the viewpoint of polymerizability and mechanical strength of polyimide, diamines having a trifluoromethoxy group (CF3-O-) are preferred, and among these, diamines in which the oxygen atom of the trifluoromethoxy group is bonded to a carbon atom of an aromatic ring are preferred. From the viewpoint of reactivity, it is preferable that a diamine in which a trifluoromethoxy group is bonded to a carbon atom of an aromatic ring does not have a fluorine atom directly bonded to the aromatic ring to which the trifluoromethoxy group is bonded, and it is particularly preferable that the diamine does not contain any fluorine atoms other than those in the trifluoromethoxy group. Examples of specific diamines in which a trifluoromethoxy group is bonded to a carbon atom of an aromatic ring include trifluoromethoxy-substituted benzidine and trifluoromethoxy-substituted phenylenediamine.
[0039] Examples of trifluoromethoxy-substituted benzidines include 2-(trifluoromethoxy)benzidine, 3-(trifluoromethoxy)benzidine, 2,3-bis(trifluoromethoxy)benzidine, 2,5-bis(trifluoromethoxy)benzidine, 2,6-bis(trifluoromethoxy)benzidine, 2,3,5-tris(trifluoromethoxy)benzidine, 2,3,6-tris(trifluoromethoxy)benzidine, 2,3,5,6-tetrakis(trifluoromethoxy)benzidine, 2,2'-bis(trifluoromethoxy)benzidine (TFMOB), 3,3'-bis(trifluoromethoxy)benzidine, and 2,3'-bis(trifluoromethoxy)benzidine. Examples include 0(trifluoromethoxy)benzidine, 2,2',3-tris(trifluoromethoxy)benzidine, 2,3,3'-tris(trifluoromethoxyl)benzidine, 2,2',5-tris(trifluoromethoxy)benzidine, 2,2',6-tris(trifluoromethoxy)benzidine, 2,3',5-tris(trifluoromethoxy)benzidine, 2,3',6-tris(trifluoromethoxy)benzidine, 2,2',3,3'-tetrakis(trifluoromethoxy)benzidine, 2,2',5,5'-tetrakis(trifluoromethoxy)benzidine, and 2,2',6,6'-tetrakis(trifluoromethoxy)benzidine.
[0040] Examples of trifluoromethoxy-substituted phenylenediamines include 1,2-diamino-4-(trifluoromethoxy)benzene, 1,3-diamino-4-(trifluoromethoxy)benzene, 1,4-diamino-2-(trifluoromethoxy)benzene, 1,4-diamino-2,3-bis(trifluoromethoxy)benzene, 1,4-diamino-2,5-bis(trifluoromethoxy)benzene, 1,4-diamino-2,6-bis(trifluoromethoxy)benzene, 1,4-diamino-2,3,5-tris(trifluoromethoxy)benzene, and 1,4-diamino-2,3,5,6-tetrakis(trifluoromethoxy)benzene.
[0041] Among the specific diamines mentioned above, trifluoromethoxy-substituted benzidines are preferred from the viewpoint of polyimide expandability and mechanical strength. In particular, those having a trifluoromethoxy group at the 2nd or 3rd position of biphenyl are preferred from the viewpoint of polyimide solubility in organic solvents and compatibility with transparent resins other than polyimide, with 2,2'-bis(trifluoromethoxy)benzidine (hereinafter referred to as "TFMOB"), 3,3'-bis(trifluoromethoxy)benzidine, and 2,3'-bis(trifluoromethoxy)benzidine being more preferred, and TFMOB being particularly preferred. By having a trifluoromethoxy group at the 2nd or 3rd position of biphenyl, in addition to the decrease in π electron density due to the electron-withdrawing properties of the trifluoromethoxy group, π-π stacking between benzene rings is inhibited due to the steric hindrance of the trifluoromethoxy group, so the absorption edge wavelength is shifted to a shorter wavelength, and the coloration of the polyimide can be reduced. Furthermore, TFMOB reduces the coloration of polyimide because the steric hindrance between the trifluoromethoxy groups at the 2 and 2' positions of biphenyl causes the bond between the two benzene rings of biphenyl to twist, reducing the planarity of the π-conjugated structure. This causes the absorption edge wavelength to shift to a shorter wavelength.
[0042] The amount of specific diamine relative to the total amount of diamine components in the polyimide is preferably 10 mol% or more, more preferably 30 mol% or more, even more preferably 50 mol% or more, and may also be 60 mol% or more, 70 mol% or more, or 80 mol% or more, or even 100 mol%. In particular, it is preferable that the amount of trifluoromethoxy group-containing diamine be within this range, and especially preferable that the amount of trifluoromethoxy-substituted benzidine be within this range. The higher the ratio of specific diamine, the more the discoloration is suppressed, and the mechanical strength of the optical film, such as pencil hardness, elastic modulus, breaking strength, and elongation at break, may improve.
[0043] (Diamines other than specified diamines) Polyimides may contain diamines other than specified diamines as diamine components. From the viewpoint of environmental safety of polyimides, those that do not contain -C-CF3 and -C-CF2-C- are preferred, and those that do not contain fluorine atoms are particularly preferred.
[0044] Examples of diamines that do not contain a fluorine atom include 2,2'-dimethylbenzidine, o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, o-xylylenediamine, m-xylylenediamine, p-xylylenediamine, 3,3'-diaminodiphenylsulfone, 3,4'-diaminodiphenylsulfone, 4,4'-diaminodiphenylsulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone, and 4,4'-bis[4-(4-amino-α,α-dimethylbenzyl) [Phenoxy]diphenylsulfone, 4,4'-bis[4-(4-aminophenoxy)phenoxy]diphenylsulfone, 3,3'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfide, bis[4-(3-aminophenoxy)phenyl]sulfide, bis[4-(4-aminophenoxy)phenyl]sulfide, 3,3'-diaminobenzophenone, 4,4'-diaminobenzophenone, 3,4'-diaminobenzophenone, 1,3-bis(3-aminobenzoyl)benzene, 1,3-bis s(4-aminobenzoyl)benzene, 1,4-bis(3-aminobenzoyl)benzene, 1,4-bis(4-aminobenzoyl)benzene, bis[4-(3-aminophenoxy)phenyl]ketone, bis[4-(4-aminophenoxy)phenyl]ketone, 1,3-bis[4-(3-aminophenoxy)benzoyl]benzene, 1,3-bis[4-(4-aminophenoxy)benzoyl]benzene, 1,4-bis[4-(3-aminophenoxy)benzoyl]benzene, 1,4-bis[4-(4-aminophenoxy)benzoyl]benzene, 3,3'- Diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(3-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(3-aminophenoxy)biphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, bis[4-(3-aminophenoxy)phenyl] ether, bis[4-(4-aminophenoxy)phenyl] ether, 3,3'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 1,1-bis(3-aminophenyl)ethane, 1,1-bis(4-aminophenyl)ethane, 1-(3-aminophenyl)-1-(4-aminophenyl)ethane, 1,2-bis(4-aminophenyl)ethane, 2,2-bis(3-aminophenyl)propane, 2,2-bis(4-aminophenyl)propane, 2-(3-aminophenyl)-2-(4-aminophenyl)propane, 1,1-bis(4-aminophenyl)cyclohexane, 1 ,3-bis(3-amino-α,α-dimethylbenzyl)benzene, 1,3-bis(4-amino-α,α-dimethylbenzyl)benzene, 1,4-bis(3-amino-α,α-dimethylbenzyl)benzene, 1,4-bis(4-amino-α,α-dimethylbenzyl)benzene, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 1,3-bis[4-(3-aminophenoxy)-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-aminophenoxy)-α ,α-dimethylbenzyl]benzene, 1,4-bis[4-(3-aminophenoxy)-α,α-dimethylbenzyl]benzene, 1,4-bis[4-(4-aminophenoxy)-α,α-dimethylbenzyl]benzene, 9,9-bis(4-aminophenyl)fluorene, 9,9-bis(4-amino-3-methylphenyl)fluorene, 9,9-bis(3-amino-4-hydroxyphenyl)fluorene, 9,9-bis(4-amino-3-hydroxyphenyl)fluorene, 9,9-bis[4-(4-aminophenoxy)phenyl]fluorene, spiro[9 H-Fluorene-9,9'-[9H]xanthene]-3',6'-diamine, spiro[9H-fluorene-9,9'-[9H]xanthene]-2',7'-diamine, 4',5'-dimethylspiro[9H-fluorene-9,9'-[9H]xanthene]-3',6'-diamine, 4,4'-bis[4-(4-aminophenoxy)benzoyl]diphenyl ether, 4,4'-bis[4-(4-amino-α,α-dimethylbenzyl)phenoxy]benzophenone, 3,3'-diamino-4,4'-diphenoxybenzophenone, 3,3'-diamino-4,4'-Dibiphenoxybenzophenone, 3,3'-Diamino-4-phenoxybenzophenone, 3,3'-Diamino-4-biphenoxybenzophenone, 2,6-Bis(3-aminophenoxy)benzonitrile, 2,6-Bis(3-aminophenoxy)pyridine, 3,3'-Diaminobenzanilide, 3,4'-Diaminobenzanilide, 4,3'-Diaminobenzanilide, 4,4'-Diaminobenzanilide, 6,6'-Bis(3-aminophenoxy)-3,3,3',3'-Tetramethyl-1,1'-Spirobindan, 6,6'-Bis(4-amino Phenoxy)-3,3,3',3'-tetramethyl-1,1'-spirobindan, 1,2-diaminocyclohexane, 1,3-diaminocyclohexane, 1,4-diaminocyclohexane, trans-1,4-diaminocyclohexane, 1,2-bis(aminomethyl)cyclohexane, 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, isophoronediamine, bis(4-aminocyclohexyl)methane, bis(3-methyl-4-aminocyclohexyl)methane, bis(aminomethyl)norbornene, 2,6 -Bis(aminomethyl)norbornene, 2,5-Bis(aminomethyl)norbornene, 1,3-diaminoadamantane, ethylenediamine, 1,3-diaminopropane, 1,4-diaminobutane, 1,5-diaminopentane, 1,6-diaminohexane, 1,7-diaminoheptane, 1,8-diaminooctane, 1,9-diaminononane, 1,10-diaminodecane, 1,11-diaminoundecane, 1,12-diaminododecane, bis(aminomethyl)ether, bis(2-aminoethyl)ether, bis(3-aminopropyl)ether, bis[(2- [aminomethoxy)ethyl] ether, bis[2-(2-aminoethoxy)ethyl] ether, bis[2-(3-aminopropoxy)ethyl] ether, 1,2-bis(aminomethoxy)ethane, 1,2-bis(2-aminoethoxy)ethane, 1,2-bis[2-(aminomethoxy)ethoxy]ethane, 1,2-bis[2-(2-aminoethoxy)ethoxy]ethane, ethylene glycol bis(3-aminopropyl) ether, diethylene glycol bis(3-aminopropyl) ether, triethylene glycol bis(3-aminopropyl) ether, 1,Examples include 3-bis(3-aminopropyl)tetramethyldisiloxane, 1,3-bis(4-aminobutyl)tetramethyldisiloxane, α,ω-bis(3-aminopropyl)polydimethylsiloxane, and α,ω-bis(4-aminobutyl)polydimethylsiloxane.
[0045] For example, the mechanical strength of polyimide can be improved by using aromatic diamines in addition to specific diamines. Among aromatic diamines, 2,2'-dimethylbenzidine, p-phenylenediamine, 4,4'-diaminodiphenyl ether, and 3,4'-diaminodiphenyl ether are preferred, and these may be used in combination.
[0046] When using aromatic diamines, from the viewpoint of the mechanical strength of polyimide, the amount of aromatic diamine relative to the total amount of diamine components is preferably 1 mol% or more, more preferably 3 mol% or more, even more preferably 5 mol% or more, and may be 10 mol% or more, 12 mol% or more, or 15 mol% or more. From the viewpoint of the solubility and transparency of polyimide, the amount of aromatic diamine relative to the total amount of diamine components is preferably 50 mol% or less, more preferably 30 mol% or less, and may be 20 mol% or less, 10 mol% or less, or even not included at all. The amount of aromatic diamine required to ensure compatibility with transparent resins other than polyimide may vary depending on the transparent resin other than polyimide and the type of aromatic diamine.
[0047] For example, by using diaminodiphenylsulfone in addition to specific diamines as the diamine, the mechanical strength and transparency of the polyimide may be improved. Among diaminodiphenylsulfones, 3,3'-diaminodiphenylsulfone (3,3'-DDS) and 4,4'-diaminodiphenylsulfone (4,4'-DDS) are preferred, and these may be used in combination.
[0048] When diaminodiphenylsulfone is used in addition to specific diamines, from the viewpoint of transparency and mechanical strength of the polyimide, the amount of diaminodiphenylsulfone relative to the total amount of diamine components is preferably 1 mol% or more, more preferably 3 mol% or more, even more preferably 5 mol% or more, and may be 10 mol% or more, 12 mol% or more, or 15 mol% or more. From the viewpoint of solubility of the polyimide, the amount of diaminodiphenylsulfone relative to the total amount of diamine components is preferably 50 mol% or less, more preferably 30 mol% or less, and may be 20 mol% or less, 10 mol% or less, or may not be present at all. The amount of diaminodiphenylsulfone required to ensure compatibility with transparent resins other than polyimide may vary depending on the transparent resin other than polyimide and the type of diaminodiphenylsulfone.
[0049] For example, by using a diamine having a fluorene structure in addition to a specific diamine, the solubility in solvents, transparency, and mechanical strength of the polyimide may be improved. Preferred diamines having a fluorene structure include 9,9-bis(4-aminophenyl)fluorene, 9,9-bis[4-(4-aminophenoxy)phenyl]fluorene, 9,9-bis(3-amino-4-hydroxyphenyl)fluorene, and 9,9-bis(4-amino-3-methylphenyl)fluorene, and these may be used in combination.
[0050] When using a diamine having a fluorene structure in addition to a specific diamine, from the viewpoint of the solubility and transparency of the polyimide in the solvent, the amount of diamine having a fluorene structure relative to the total amount of diamine components is preferably 1 mol% or more, more preferably 3 mol% or more, even more preferably 5 mol% or more, and may be 10 mol% or more, 15 mol% or more, or 30 mol% or more. From the viewpoint of the mechanical strength of the polyimide, the amount of diamine having a fluorene structure relative to the total amount of diamine components is preferably 90 mol% or less, more preferably 70 mol% or less, and may be 50 mol% or less, 30 mol% or less, or may not be present at all. The amount of diamine having a fluorene structure required to ensure compatibility with transparent resins other than polyimide may vary depending on the transparent resin other than polyimide and the type of diamine having a fluorene structure.
[0051] For example, the transparency of polyimides can be improved by using alicyclic diamines in addition to specific diamines. Among alicyclic diamines, isophorone diamine, 1,4-diaminocyclohexane, 1,4-bis(aminomethyl)cyclohexane, and bis(4-aminocyclohexyl)methane are preferred, and these may be used in combination.
[0052] When using alicyclic diamines, from the viewpoint of polyimide solubility and transparency, the amount of alicyclic diamine relative to the total amount of diamine components is preferably 1 mol% or more, more preferably 3 mol% or more, even more preferably 5 mol% or more, and may be 10 mol% or more, 12 mol% or more, or 15 mol% or more. From the viewpoint of the mechanical strength of polyimide, the amount of alicyclic diamine relative to the total amount of diamine components is preferably 70 mol% or less, more preferably 50 mol% or less, and may be 30 mol% or less, 20 mol% or less, or may not be present at all. The amount of alicyclic diamine required to ensure compatibility with transparent resins other than polyimide may vary depending on the transparent resin other than polyimide and the type of alicyclic diamine.
[0053] The total amount of specific diamines, aromatic diamines, diaminodiphenylsulfone, diamines having a fluorene structure, and alicyclic diamines relative to the total amount of diamine components in polyimide is preferably 70 mol% or more, more preferably 80 mol% or more, even more preferably 90 mol% or more, and may be 95 mol% or more or 99 mol% or more, or even 100 mol%.
[0054] Polyimides may contain fluorine-containing diamines other than specified diamines as their diamine component. However, from the viewpoint of environmental safety of polyimides, the amount of fluorine-containing diamines other than specified diamines relative to the total amount of diamine components in polyimides is preferably 30 mol% or less, more preferably 20 mol% or less, even more preferably 10 mol% or less, and may be 5 mol% or less, 1 mol% or less, or 0.5 mol% or less. Polyimides may also not contain fluorine-containing diamines other than specified diamines as their diamine component.
[0055] Among fluorine atom-containing diamines, those having a structure in which a trifluoromethyl group is bonded to a carbon atom (-C-CF3) and / or a structure in which carbon atoms are bonded to both ends of a difluoromethylene group (-C-CF2-C-) have low degradability and raise concerns about environmental safety. From the viewpoint of improving the transparency and solubility of polyimides, general soluble polyimides contain diamines as diamine components that have a structure in which CF3- or -C(CF3)2- is directly bonded to the carbon atom of the aromatic ring (for example, trifluoromethoxy-substituted benzidines such as 2,2'-bis(trifluoromethyl)benzidine, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane). However, from the viewpoint of the environmental safety of polyimides, it is preferable that they substantially do not contain these diamines. The amount of diamine in which CF3- or -C(CF3)2- is directly bonded to the carbon atom of the aromatic ring, relative to the total amount of diamine components in the polyimide, is preferably less than 0.5 mol%, and may be 0.3 mol% or less, 0.1 mol% or less, or 0.05 mol% or less, or even 0.
[0056] <Tetracarboxylic acid dianhydride> (Specific tetracarboxylic dianhydride) The tetracarboxylic dianhydride component of polyimide is not particularly limited, but from the viewpoint of enhancing environmental safety while providing solubility in organic solvents, it is preferable that the tetracarboxylic dianhydride component includes one or more tetracarboxylic dianhydrides selected from the group consisting of bisphenol-type tetracarboxylic dianhydrides, bis(trimellitic anhydride) esters, and tetracarboxylic dianhydrides having a fluorene structure. Hereinafter, these tetracarboxylic dianhydrides will be referred to as "specific tetracarboxylic dianhydrides."
[0057] Bisphenol-type tetracarboxylic dianhydrides are compounds represented by the following general formula (1), and can be obtained, for example, by the reaction of two hydroxyl groups of bisphenols with iodoisobenzofuran-1,3-dione.
[0058] [ka]
[0059] In general formula (1), A is any divalent organic group, with phenyl groups bonded to the carbon atoms of A at both ends. p is 1 or 2. 1a , R 1b , R 2a and R 2b Each of these is an independent arbitrary substituent, and from the viewpoint of polyimide solubility, alkyl groups, phenyl groups, alkoxy groups, or halogens having 1 to 10 carbon atoms are preferred. m1 and m2 are each independent integers from 0 to 3, and n1 and n2 are each independent integers from 0 to 4.
[0060] Examples of divalent organic group A are shown below (a), (b), and (c). R in (a) 3a and R 3b Each of these is independently a hydrogen atom, a C1-C10 alkyl group, or a phenyl group. (b) R 4R is an alkyl group having 1 to 10 carbon atoms, and k is an integer from 0 to 10. If k is 2 or greater, multiple R 4 They may be the same or they may be different.
[0061] [ka]
[0062] From the viewpoint of polyimide solubility, 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic acid anhydride (BPADA) is particularly preferred as the bisphenol-type tetracarboxylic dianhydride.
[0063] Bis(trimellitic anhydride) esters are represented by the following general formula (2).
[0064] [ka]
[0065] In general formula (2), B is any divalent organic group, with carboxyl groups bonded to the carbon atoms of B at both ends. Specific examples of divalent organic group B include (i) to (viii) below.
[0066] [ka]
[0067] The groups represented by formulas (i) to (viii) are diols from which two hydroxyl groups have been removed. For example, the group represented by formula (i) is a hydroquinone derivative which may have substituents on the benzene ring from which two hydroxyl groups have been removed.
[0068] In equations (i) and (ii), R 1 , R 2a and R 2bEach of these is independently an alkyl group, alkoxy group, or halogen having 1 to 4 carbon atoms, and m, n1, and n2 are each independently integers from 0 to 4. In formulas (iii), (iv), and (v), R 3a and R 3b k1 and k2 are each independently arbitrary substituents, and from the viewpoint of polyimide solubility, C1-C10 alkyl groups, phenyl groups, alkoxy groups, or halogens are preferred. 4 is an alkyl group, alkoxy group, or halogen, and j is an integer between 0 and 10.
[0069] The bis(trimellitic anhydride) ester is preferably an aromatic ester, and as B in general formula (2), among (i) to (viii) above, (i) to (iv) are preferred, and among these, (i) to (iv) are particularly preferred, with (i) and (ii) being especially preferred.
[0070] When B is a group represented by general formula (i), from the viewpoint of the mechanical properties of the resin composition, the bis(trimellitic anhydride) ester of general formula (2) is preferably 1,4-phenylenebis(1,3-dioxo-1,3-dihydroisobenzofuran-5-carboxylate)(TMHQ), which is represented by the following formula (2-1).
[0071] [ka]
[0072] When B is a group represented by formula (ii), from the viewpoint of polyimide solubility, the bis(trimellitic anhydride) ester of general formula (2) is preferably 2,2',3,3',5,5'-hexamethylbiphenyl-4,4'-diylbis(1,3-dioxo-1,3-dihydroisobenzofuran-5-carboxylate) (TAHMBP), which is represented by the following formula (2-2).
[0073] [ka]
[0074] When B is a group represented by formula (iii), from the viewpoint of polyimide solubility, the bis(trimellitic anhydride) ester of general formula (2) is preferably bisphenol Z bis(trimellitic anhydride) (BPZ-TME) represented by the following formulas (2-3).
[0075] [ka]
[0076] When B is a group represented by formula (iv), from the viewpoint of polyimide solubility, the bis(trimellitic anhydride) ester of general formula (2) is preferably 5,5'-[cyclododecylidenebis(2-methyl-4,1-phenylene)]bis(1,3-dihydro-1,3-dioxo-5-isobenzofurancarboxylate) (TBIS-DMPN) represented by the following formulas (2-4).
[0077] [ka]
[0078] A tetracarboxylic dianhydride having a fluorene structure is a compound having a fluorene structure between two acid anhydride groups. Furthermore, if the bisphenol-type tetracarboxylic dianhydride of general formula (1) or the bis(trimellitic anhydride) ester of general formula (2) has a fluorene structure, then the acid dianhydride is treated as a tetracarboxylic dianhydride having a fluorene structure.
[0079] Examples of tetracarboxylic dianhydrides having a fluorene structure include the acid dianhydrides represented by group (A) below, and N,N'-(9H-fluorene-9-ylidenedi-4,1-phenylene)bis[1,3-dihydro-1,3-dioxo-5-isobenzofrancarboxamide].
[0080] [ka]
[0081] (A) R 1a , R 1b , R 2a , R 2b , R 3a , R 3b , R 4a and R 4b Each of these is an independent of any substituent, and from the viewpoint of polyimide solubility, alkyl groups, phenyl groups, alkoxy groups, or halogens having 1 to 10 carbon atoms are preferred. m1 and m2 are each independently integers from 0 to 3. n1 and n2 are each independently integers from 0 to 4. k1 and k2 are each independently integers from 0 to 2. j1 and j2 are each independently integers from 0 to 4.
[0082] R 5a and R 5b R is an alkylene group or a phenylene group, 5a and R 5b They may be the same or different. p1 and p2 are independently 0 or 1. 6 represents a carbonyl group, and q1 and q2 are independently either 0 or 1.
[0083] (A) Among the group, the following tetracarboxylic dianhydrides having a fluorene structure are selected because they have a small molecular weight, a relatively high proportion of fluorene structures, and improve the solubility and transparency of polyimides, as well as compatibility with transparent resins other than polyimides. 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, 9,9-bis[4-(3,4-dicarboxyphenoxy)phenyl]fluorene dianhydride, spiro[11H-difluoro[3,4-b:3',4'-i]xanthene-11,9'-fluorene]-1,3,7,9-tetraone, 5,5'-spiro[ 9H-fluorene-9,9'-[9H]xanthene]-3',6'-diyrbis(1,3-dihydro-1,3-dioxo-5-isobenzofuran carboxylate), 5,5'-[9H-fluorene-9-ylidenebis(2-methyl-4,1-phenylene)]bis(1,3-dihydro-1,3-dioxo-5-isobenzofuran carboxylate), and 5,5'-[9H-fluorene-9-ylidenebis(4,1-phenyleneoxy-4,1-phenylene)]bis(1,3-dihydro-1,3-dioxo-5-isobenzofuran carboxylate) are preferred.
[0084] Polyimides containing the aforementioned specific diamine as the diamine component and a specific tetracarboxylic dianhydride as the tetracarboxylic dianhydride component tend to exhibit solubility in organic solvents, as well as high transparency and compatibility with transparent resins other than polyimides.
[0085] From the viewpoint of solubility in organic solvents, transparency, and compatibility with transparent resins other than polyimides, among specific tetracarboxylic dianhydrides, the following are considered: 4,4'-(4,4'-isopropylidene diphenoxy)diphthalic acid anhydride (BPADA), 1,4-phenylenebis(1,3-dioxo-1,3-dihydroisobenzofuran-5-carboxylate) (TMHQ), 2,2',3,3',5,5'-hexamethylbiphenyl-4,4'-diylbis(1,3-dioxo-1,3-dihydroisobenzofuran-5-carboxylate) (TAHMBP), bisphenol Z bis(trimellitic anhydride) (BPZ-TME), and 5,5'-[cyclododecylidenebis(2-methyl-4,1-phenylene)]bis(1,3-dihydro-1,3-dioxo-5-isobenzofurancarboxylate). (TBIS-DMPN), 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride (BPAF), 9,9-bis[4-(3,4-dicarboxyphenoxy)phenyl]fluorene dianhydride (BPF-PA), 5,5'-[9H-fluorene-9-ylidenebis(2-methyl-4,1-phenylene)]bis(1,3-dihydro-1,3-dioxo-5-isobenzofurancarboxyl Silate) (TBIS-MPN), 5,5'-spiro[9H-fluorene-9,9'-[9H]xanthene]-3',6'-diirbis(1,3-dihydro-1,3-dioxo-5-isobenzofurancarboxylate) (TBIS-RXN), and spiro[11H-difl[3,4-b:3',4'-i]xanthene-11,9'-fluorene]-1,3,7,9-tetraone are preferred.
[0086] From the viewpoint of the UV resistance of polyimide, among specific tetracarboxylic dianhydrides, bisphenol-type tetracarboxylic dianhydrides and acid dianhydrides having a fluorene structure (excluding those having an ester structure) are preferred. From the viewpoint of the mechanical strength of polyimide, BPADA, BPAF, and BPF-PA are preferred, and from the viewpoint of solubility in solvents, BPADA and BPAF are particularly preferred. These tetracarboxylic dianhydrides do not have ester bonds and do not undergo fleece transition due to UV light, so discoloration is less likely to occur when polyimide is exposed to UV light. Furthermore, from the viewpoint of compatibility with transparent resins other than polyimide, bisphenol-type tetracarboxylic dianhydrides such as BPADA and acid dianhydrides having a fluorene structure such as BPAF and BPF-PA are preferred as specific tetracarboxylic dianhydrides.
[0087] From the viewpoint of the solubility of polyimide in organic solvents and compatibility with transparent resins other than polyimide, the total amount of specific tetracarboxylic dianhydride relative to the total amount of tetracarboxylic dianhydride components is preferably 15 mol% or more, more preferably 30 mol% or more, even more preferably 50 mol% or more, and may be 60 mol% or more, 70 mol% or more, 80 mol% or more, 90 mol% or more, 95 mol% or more, or 100 mol%. The total amount of specific tetracarboxylic dianhydride relative to the total amount of tetracarboxylic dianhydride components may be 95 mol% or less, 90 mol% or less, 85 mol% or less, 80 mol% or less, 75 mol% or less, or 70 mol% or less.
[0088] (Tetracarboxylic acid dianhydrides other than specific tetracarboxylic acid dianhydrides) Polyimides may contain tetracarboxylic dianhydrides other than specific tetracarboxylic dianhydrides as tetracarboxylic dianhydrides. Examples of such tetracarboxylic dianhydrides include alicyclic tetracarboxylic dianhydrides, aromatic tetracarboxylic dianhydrides, and linear aliphatic tetracarboxylic dianhydrides. From the viewpoint of environmental safety of polyimides, those that do not contain -C-CF3 and -C-CF2-C- are preferred, and those that do not contain fluorine atoms are particularly preferred.
[0089] Alicyclic tetracarboxylic dianhydrides only need to have at least one alicyclic structure, and may have both an alicyclic and an aromatic ring in a single molecule. The alicyclic structure may be polycyclic and may have a spiro structure.Other alicyclic tetracarboxylic dianhydrides besides specific tetracarboxylic dianhydrides include 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride, 1,3-dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-tetramethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,4,5-cyclohexanetetracarboxylic dianhydride, 3,3',4,4'-bicyclohexanetetracarboxylic dianhydride, norbornane-2-spiro-α- Cyclopentanone-α'-spiro-2”-norbornane-5,5”,6,6”-tetracarboxylic dianhydride, 2,2'-binorbornane-5,5',6,6'-tetracarboxylic dianhydride, 3-(carboxymethyl)-1,2,4-cyclopentanetricarboxylic acid-1,4:2,3-dianhydride, bicyclo[2.2.2]octa-7-ene-2,3,5,6-tetracarboxylic dianhydride, bicyclo[2.2.1]heptane-2,3,5,6-tetracarboxylic dianhydride, bicyclo[2.2.2]octane-2,3,5,6-tetracarboxylic dianhydride Product, 5-(2,5-dioxotetrahydrofuryl)-3-methyl-3-cyclohexene-1,2-dicarboxylic acid anhydride, 3,5,6-tricarboxynorbornane-2-acetic acid 2,3:5,6-dianhydride, decahydro-1,4,5,8-dimethanonaphthalene-2,3,6,7-tetracarboxylic acid dianhydride, tricyclo[6.4.0.0(2,7)]dodecane-1,8:2,7-tetracarboxylic acid dianhydride, octahydro-1H,3H,8H,10H-biphenyleno[4a,4b-c:8a,8b-c']difuran-1,3,8,10-tetron Examples include decahydro[2]benzopyrano[6,5,4,-def][2]benzopyran-1,3,6,8-tetron, 5,5'-(1,2-ethanediyl)bis(octahydro-1,3-dioxo-5-isobenzofurancarboxylate), cyclohexane-1,4-diylbis(1,4-phenylene)bis(1,3-dioxooctahydroisobenzofuran-5-carboxylate), and 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic acid dianhydride.The inclusion of alicyclic tetracarboxylic dianhydrides in addition to specific tetracarboxylic dianhydrides as a tetracarboxylic dianhydride component tends to improve the mechanical strength of polyimides. Furthermore, the inclusion of alicyclic tetracarboxylic dianhydrides as a tetracarboxylic dianhydride component in polyimides may improve their compatibility with other transparent resins.
[0090] Among alicyclic tetracarboxylic dianhydrides, from the viewpoint of polyimide transparency and mechanical strength, 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA), 1,2,3,4-cyclopentanetetracarboxylic dianhydride (CPDA), 1,2,4,5-cyclohexanetetracarboxylic dianhydride (H-PMDA), 3,3',4,4'-bicyclohexanetetracarboxylic dianhydride (H-BPDA), norbornane-2-spiro-α-cyclopentanone-α'-spiro-2”-norbornane-5,5”,6,6”-tetracarboxylic dianhydride (CpODA), and 2,2'-binorbornane-5,5',6,6'-tetracarboxylic dianhydride are selected. (BNBDA), decahydro-1,4,5,8-dimethanonaphthalene-2,3,6,7-tetracarboxylic dianhydride (DNDA), bicyclo[2.2.2]octa-7-ene-2,3,5,6-tetracarboxylic dianhydride (BEDA), bicyclo[2.2.2]octane-2,3,5,6-tetracarboxylic dianhydride (BODA), and 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride (TDA-100) are preferred. Among these, tetracarboxylic anhydrides in which two acid anhydride groups are bonded to one alicyclic ring are preferred from the viewpoint of mechanical strength, and CBDA is particularly preferred.
[0091] When using alicyclic tetracarboxylic dianhydrides in addition to specific tetracarboxylic dianhydrides, the amount of alicyclic tetracarboxylic dianhydrides relative to the total amount of tetracarboxylic dianhydrides may be 1 mol% or more, 3 mol% or more, 5 mol% or more, 10 mol% or more, 12 mol% or more, or 15 mol% or more. The higher the amount of alicyclic tetracarboxylic dianhydrides, the higher the transparency of the polyimide tends to be. From the viewpoint of ensuring the solubility of the polyimide in organic solvents, the amount of alicyclic tetracarboxylic dianhydrides relative to the total amount of tetracarboxylic dianhydrides is preferably 80 mol% or less, more preferably 60 mol% or less, even more preferably 50 mol% or less, and may also be 40 mol% or less, 30 mol% or less, or 20 mol% or less.
[0092] Aromatic tetracarboxylic dianhydrides other than specific tetracarboxylic dianhydrides include pyromellitic acid dianhydride, merophanic acid dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, terphenyltetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, and 2,3,6,7-anthrace Diantetracarboxylic acid dianhydride, 1,2,7,8-phenanthrenetetracarboxylic acid dianhydride, 3,4,9,10-perylenetetracarboxylic acid dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic acid dianhydride, 3,4'-thiodiphthalic acid anhydride, 4,4'-thiodiphthalic acid anhydride, 3,3'-thiodiphthalic acid anhydride, 4,4'-bis(3,4-dicarboxyphenoxy)diphenyl sulfide dianhydride, 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride, 2,2',3,3' -Benzophenonetetracarboxylic dianhydride, 1,3-bis(3,4-dicarboxybenzoyl)benzene dianhydride, 1,4-bis(3,4-dicarboxybenzoyl)benzene dianhydride, 3,4'-oxydiphthalic anhydride (3,4'-ODPA), 4,4'-oxydiphthalic anhydride (4,4'-ODPA), 3,3'-oxydiphthalic anhydride (3,3'-ODPA), 1,4-bis(3,4-dicarboxyphenoxy)benzene dianhydride, 4,4'-bis(3,4-dicarboxyphenoxy) Examples include phenyl dianhydride, 4,4'-bis(3,4-dicarboxyphenoxy)benzophenone dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, and 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride.
[0093] Among these aromatic tetracarboxylic dianhydrides, 3,4'-ODPA, 4,4'-ODPA, and 3,3'-ODPA are preferred from the viewpoint of polyimide solubility, and pyromellitic dianhydride and merophanic dianhydride are preferred from the viewpoint of mechanical strength, with pyromellitic dianhydride being particularly preferred.
[0094] When using aromatic tetracarboxylic dianhydrides other than the specified tetracarboxylic dianhydrides in addition to the specified tetracarboxylic dianhydrides, the amount of aromatic tetracarboxylic dianhydrides other than the specified tetracarboxylic dianhydrides relative to the total amount of tetracarboxylic dianhydrides may be 1 mol% or more, 3 mol% or more, 5 mol% or more, 10 mol% or more, 12 mol% or more, or 15 mol% or more. The higher the amount of aromatic tetracarboxylic dianhydrides, the higher the mechanical strength of the polyimide tends to be. From the viewpoint of ensuring the solubility of the polyimide in organic solvents, the amount of aromatic tetracarboxylic dianhydrides other than the specified tetracarboxylic dianhydrides relative to the total amount of tetracarboxylic dianhydrides is preferably 80 mol% or less, more preferably 60 mol% or less, even more preferably 50 mol% or less, and may also be 40 mol% or less, 30 mol% or less, or 20 mol% or less.
[0095] Examples of linear aliphatic tetracarboxylic dianhydrides include ethylenetetracarboxylic dianhydride, 1,2,3,4-butanetetracarboxylic dianhydride, and meso-butane-1,2,3,4-tetracarboxylic dianhydride.
[0096] When using a linear aliphatic tetracarboxylic dianhydride other than the specified tetracarboxylic dianhydride in addition to the specified tetracarboxylic dianhydride, the amount of the linear aliphatic tetracarboxylic dianhydride other than the specified tetracarboxylic dianhydride relative to the total amount of tetracarboxylic dianhydride components may be 1 mol% or more, 3 mol% or more, 5 mol% or more, 10 mol% or more, 12 mol% or more, or 15 mol% or more. The higher the amount of linear aliphatic tetracarboxylic dianhydride, the higher the transparency of the polyimide tends to be. From the viewpoint of ensuring the mechanical strength of the polyimide, the amount of the linear aliphatic tetracarboxylic dianhydride other than the specified tetracarboxylic dianhydride relative to the total amount of tetracarboxylic dianhydride components is preferably 80 mol% or less, more preferably 60 mol% or less, even more preferably 50 mol% or less, and may also be 40 mol% or less, 30 mol% or less, or 20 mol% or less.
[0097] The amount of fluorine-containing tetracarboxylic dianhydride relative to the total amount of tetracarboxylic dianhydride components in the polyimide is preferably 30 mol% or less, more preferably 20 mol% or less, even more preferably 10 mol% or less, and may also be 5 mol% or less, 1 mol% or less, or 0.5 mol% or less. The polyimide may also not contain fluorine-containing tetracarboxylic dianhydride as its tetracarboxylic dianhydride component.
[0098] Among fluorine atom-containing tetracarboxylic dianhydrides, those having a structure in which a trifluoromethyl group is bonded to a carbon atom (-C-CF3) and / or a structure in which carbon atoms are bonded to both ends of a difluoromethylene group (-C-CF2-C-) have low degradability and raise concerns about environmental safety. In particular, acid dianhydrides having a structure in which CF3- or -C(CF3)2- is directly bonded to a carbon atom of an aromatic ring (e.g., 5,5'-[2,2'-bis(trifluoromethyl)[1,1'-biphenyl]-4,4'-diyl]bis(1,3-dihydro-1,3-dioxo-5-isobenzofuran carboxylate), 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 9,9-bis(trifluoromethyl)xanthenetetracarboxylic dianhydride) have low environmental degradability, so from the viewpoint of the environmental safety of polyimides, it is preferable that they substantially do not contain these acid dianhydrides. The amount of acid dianhydride in which CF3- or -C(CF3)2- is directly bonded to the carbon atom of the aromatic ring, relative to the total amount of acid dianhydride components of the polyimide, is preferably less than 0.5 mol%, and may be 0.3 mol% or less, 0.1 mol% or less, or 0.05 mol% or less, or even 0.
[0099] <Content of specific fluorine structures in polyimides> As mentioned above, the diamine components are CF3-O-, -(CF2-O) n -, and -O-(CF2-CF2-O) n Polyimides containing diamines (specific diamines) having one or more structures selected from the above list exhibit solubility in organic solvents and compatibility with transparent resins other than polyimides, without substantially containing structures such as -C-CF3, -C-CF2-C-.
[0100] To reduce the environmental persistence of fluorine-containing compounds, it is preferable that polyimides use a small amount of monomers (diamines and acid dianhydrides) having specific fluorine structures. Specific fluorine structures are those obtained by excluding structures containing only the components of structural formula (i) below from those having a trifluoromethyl group (CF3-), and those obtained by excluding structures containing only the components of structural formula (ii) below from those having a difluoromethylene group (-CF2-). CF3-X (i) X-CF2-X' (ii)
[0101] In formulas (i) and (ii), X is -OR or -NRR', and in formula (ii), X' is one of -H, -CH3, aromatic, -C(O)-, -OR'', -SR'', and NR''R'''. R, R', R'', and R'''' are each independently one of -H, -CH3, -CH2-, aromatic, or -C(O)-.
[0102] From the viewpoint of improving environmental degradability, the amount of fluorine atoms contained in the specific fluorine structure per 1 kg of polyimide is preferably less than 500 mg, more preferably less than 300 mg, even more preferably less than 100 mg, and particularly preferably less than 50 mg.
[0103] <Preparation of polyimides> Polyamic acid, a precursor to polyimide, is obtained by the reaction of a diamine with a tetracarboxylic dianhydride, and polyimide is obtained by dehydration cyclization (imidization) of the polyamic acid. The method for preparing polyamic acid is not particularly limited, and any known method can be applied. For example, a polyamic acid solution can be obtained by dissolving a diamine and a tetracarboxylic dianhydride in approximately equimolar amounts (molar ratio of 90:100 to 110:100) in an organic solvent and stirring.
[0104] The concentration of the polyamic acid solution is typically 5 to 35% by weight, preferably 10 to 30% by weight. Within this concentration range, the polyamic acid obtained by polymerization has an appropriate molecular weight, and the polyamic acid solution has an appropriate viscosity.
[0105] In the polymerization of polyamic acids, it is preferable to add the tetracarboxylic dianhydride to the diamine to suppress ring-opening of the tetracarboxylic dianhydride. When adding multiple types of diamines or multiple types of tetracarboxylic dianhydrides, they may be added all at once or in multiple steps. The various properties of the polyimide can also be controlled by adjusting the order of monomer addition.
[0106] The organic solvent used for polymerization of polyamic acid is not particularly limited, as long as it does not react with diamines and tetracarboxylic dianhydrides and can dissolve polyamic acid. Examples of organic solvents include urea-based solvents such as methylurea and N,N-dimethylethylurea; sulfoxide or sulfone-based solvents such as dimethyl sulfoxide, diphenyl sulfone, and tetramethylsulfone; amide-based solvents such as N,N-dimethylacetamide (DMAc), N,N-dimethylformamide (DMF), N,N'-diethylacetamide, N-methyl-2-pyrrolidone (NMP), γ-butyrolactone, and hexamethylphosphate triamide; alkyl halide-based solvents such as chloroform and dichloromethane; aromatic hydrocarbon-based solvents such as benzene and toluene; and ether-based solvents such as tetrahydrofuran, 1,3-dioxolane, 1,4-dioxane, dimethyl ether, diethyl ether, and p-cresol methyl ether. These solvents are usually used individually or in appropriate combinations of two or more as needed. From the viewpoint of polyamic acid solubility and polymerization reactivity, DMAc, DMF, NMP, etc., are preferably used.
[0107] Polyimides can be obtained by the dehydration and cyclization of polyamic acids. One method for preparing polyimides from a polyamic acid solution is to add a dehydrating agent, an imidation catalyst, etc., to the polyamic acid solution and allow imidation to proceed in the solution. The polyamic acid solution may be heated to accelerate the progression of imidation. By mixing the solution containing the polyimide produced by the imidation of polyamic acid with a poor solvent, the polyimide precipitates as a solid. By isolating the polyimide as a solid, impurities generated during the synthesis of polyamic acid, as well as residual dehydrating agents and imidation catalysts, can be washed and removed with the poor solvent, preventing discoloration and increased yellowness of the polyimide. Furthermore, by isolating the polyimide as a solid, solvents suitable for film formation, such as low-boiling point solvents, can be applied when preparing solutions for making optical films.
[0108] The molecular weight of the polyimide (weight-average molecular weight in polystyrene equivalent, measured by gel filtration chromatography (GPC)) is preferably 10,000 to 1,000,000, more preferably 20,000 to 500,000, and even more preferably 40,000 to 300,000. If the molecular weight is excessively low, the strength of the optical film may be insufficient. If the molecular weight is excessively high, the solubility of the polyimide and its compatibility with transparent resins other than polyimide may be poor.
[0109] Polyimides are preferably soluble in organic solvents. Specifically, polyimides are preferably soluble in dimethylformamide (DMF) at 23°C at a concentration of 1% by weight or more. In addition to being soluble in amide solvents such as DMF, polyimides are preferably soluble in non-amide solvents. Examples of non-amide solvents include ketone solvents such as acetone and methyl ethyl ketone, alkyl halide solvents such as chloroform and dichloromethane, and ester solvents such as ethyl acetate and γ-butyrolactone. Non-amide solvents have lower boiling points compared to amide solvents, and residual solvents are easily removed during film production; therefore, polyimides soluble in non-amide solvents can be expected to improve film productivity. Polyimides are particularly preferably soluble in dichloromethane.
[0110] From the viewpoint of thermal and photostability of resin compositions and molded articles such as films, polyimides are preferably low in reactivity. The acid value of polyimides is preferably 0.4 mmol / g or less, more preferably 0.3 mmol / g or less, and even more preferably 0.2 mmol / g or less. The acid value of polyimides may also be 0.1 mmol / g or less, 0.05 mmol / g or less, or 0.03 mmol / g or less. From the viewpoint of reducing the acid value, polyimides are preferably high in imidization rate. A low acid value enhances the stability of polyimides.
[0111] <Transparent resins other than polyimide> While transparent resins other than polyimide are not particularly limited, it is desirable that they be compatible with polyimide from the viewpoint of the transparency of the resin composition. Among these, acrylic resins and polyesters are particularly preferred from the viewpoint of mechanical properties and processability.
[0112] <Acrylic resin> Examples of acrylic resins include poly(meth)acrylic acid esters such as polymethyl methacrylate, methyl methacrylate-(meth)acrylic acid copolymers, methyl methacrylate-(meth)acrylic acid ester copolymers, methyl methacrylate-acrylic acid ester-(meth)acrylic acid copolymers, and methyl (meth)acrylate-styrene copolymers. The stereoregularity of the polymer is not particularly limited and may be isotactic, syndiotactic, or atactic.
[0113] From the viewpoint of transparency, compatibility with polyimide, and mechanical strength of molded articles such as films, acrylic resins that primarily use methyl methacrylate as a structural unit are preferred. The amount of methyl methacrylate relative to the total amount of monomer components in the acrylic resin is preferably 60% by weight or more, and may be 70% by weight or more, 80% by weight or more, 85% by weight or more, 90% by weight or more, or 95% by weight or more. The acrylic resin may also be a homopolymer of methyl methacrylate.
[0114] The acrylic resin may have imide structures or lactone ring structures introduced into it. Such modified polymers are preferably acrylic polymers in which methyl methacrylate content is within the above range, and imide structures or lactone ring structures are introduced into them. That is, in acrylic resins modified by the introduction of imide structures or lactone ring structures, the total amount of methyl methacrylate and the modified methyl methacrylate structure is preferably 60% by weight or more, and may be 70% by weight or more, 80% by weight or more, 85% by weight or more, 90% by weight or more, or 95% by weight or more. The modified polymer may be a homopolymer of methyl methacrylate in which imide structures or lactone ring structures are introduced.
[0115] Introducing an imide structure into acrylic polymers such as methyl methacrylate tends to improve the glass transition temperature of the acrylic resin. Furthermore, because the acrylic resin contains an imide structure, its compatibility with polyimides may improve. For example, a particular polyimide may not be compatible with polymethyl methacrylate, but may be compatible with acrylic resins containing a glutarimide structure.
[0116] Acrylic resins having a glutarimide structure can be obtained, for example, by heating and melting a polymethyl methacrylate resin and treating it with an imidizing agent, as described in Japanese Patent Publication No. 2010-261025. Commercially available products such as "PLEXIMID TT70" and "PLEXIMID 8805" manufactured by EVONIK can also be used as imide-modified polymethyl methacrylate.
[0117] When an acrylic resin has a glutarimide structure, the glutarimide content may be 3% or more by weight, 10% or more by weight, 20% or more by weight, 30% or more by weight, or 50% or more by weight. The glutarimide content is calculated by determining the introduction rate of the glutarimide structure (imidization rate) from the 1H-NMR spectrum of the acrylic resin and converting the imidization rate to weight. For example, in methyl methacrylate with an introduced glutarimide structure, the imidization rate Im = B / (A+B) can be determined from the area A of the peak derived from the O-CH3 proton of methyl methacrylate (around 3.5~3.8 ppm) and the area B of the peak derived from the N-CH3 proton of glutarimide (around 3.0~3.3 ppm).
[0118] From the viewpoint of heat resistance of the resin composition and molded article, the glass transition temperature of the acrylic resin is preferably 100°C or higher, more preferably 110°C or higher, and may be 115°C or higher or 120°C or higher.
[0119] From the viewpoint of solubility in organic solvents, compatibility with the above-mentioned polyimide, and strength of the molded article, the weight-average molecular weight (polystyrene equivalent) of the acrylic resin is preferably 5,000 to 5,000,000, more preferably 10,000 to 2,000,000, and may also be 30,000 to 1,000,000 or 50,000 to 500,000. If the molecular weight of the acrylic resin is too low, the durability of the resulting optical film may decrease. If the molecular weight of the acrylic resin is too high, the film-forming properties may be poor.
[0120] From the viewpoint of thermal and photostability of the resin composition and optical film, it is preferable that the acrylic resin has a low content of reactive functional groups such as ethylenically unsaturated groups and carboxyl groups. The iodine value of the acrylic resin is preferably 10.16 g / 100 g (0.4 mmol / g) or less, more preferably 7.62 g / 100 g (0.3 mmol / g) or less, and even more preferably 5.08 g / 100 g (0.2 mmol / g) or less. The iodine value of the acrylic resin may also be 2.54 g / 100 g (0.1 mmol / g) or less or 1.27 g / 100 g (0.05 mmol / g) or less. The acid value of the acrylic resin is preferably 0.4 mmol / g or less, more preferably 0.3 mmol / g or less, and even more preferably 0.2 mmol / g or less. The acid value of the acrylic resin may be 0.1 mmol / g or less, 0.05 mmol / g or less, or 0.03 mmol / g or less. A lower acid value tends to increase the stability of the acrylic resin and improve its compatibility with polyimide.
[0121] <Polyester> Polyester is a condensate of dicarboxylic acid and glycol, and has structures derived from both dicarboxylic acid and diol. From the viewpoint of ensuring the mechanical strength of molded articles such as optical films formed from the resin composition, polyester with a weight-average molecular weight (Mw, polystyrene equivalent) greater than 10,000 is preferred. The weight-average molecular weight of polyester is preferably 15,000 or more, more preferably 20,000 or more, and may be 30,000 or more. From the viewpoint of ensuring compatibility with polyimide and moldability of the resin composition into films, the weight-average molecular weight of polyester is preferably 200,000 or less, more preferably 150,000 or less, even more preferably 100,000 or less, and may be 80,000 or less.
[0122] Polyethylene terephthalate (PET), a typical polyester, is a condensate of ethylene glycol and terephthalic acid, and has high crystallinity and low solubility in organic solvents. In this embodiment, a polyester soluble in organic solvents is used. The polyester is preferably soluble in organic solvents common to polyimide, and is particularly preferably soluble in highly polar solvents such as amide solvents.
[0123] The polyester only needs to be soluble in organic solvents, and the dicarbon and diol components are not particularly limited. From the viewpoint of solubility in organic solvents, amorphous polyesters are preferred. Furthermore, from the viewpoint of bending resistance, the polyester is preferably weight-average molecular weight greater than 10,000.
[0124] (Diol) From the viewpoint of providing polyester with solubility in organic solvents, preferred diol components of polyester include diols having a chain-like alkylene group with 3 or more carbon atoms, which may be branched; diols having a chain-like alkenylene group with 3 or more carbon atoms, which may be branched; polyalkylene glycols; and diols having a cyclic structure. Hereinafter, these diols will be referred to as "specific diols."
[0125] Examples of diols having a chain-like alkylene structure with 3 or more carbon atoms, which may be branched, include propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, neopentyl glycol, and 1,6-hexanediol. Among these, diols having a chain-like alkylene structure with 5 or more carbon atoms are preferred, and among these, diols having branched alkylene groups such as neopentyl glycol are preferred. Examples of diols having a chain-like alkenylene group with 3 or more carbon atoms, which may be branched, include 2-butene-1,4-diol.
[0126] Examples of polyalkylene glycols include diethylene glycol, triethylene glycol, dipropylene glycol, and polytetramethylene ether glycol.
[0127] Examples of diols having a cyclic structure include diols having a cycloalkylene structure such as 1,4-cyclohexanediol and 1,4-cyclohexanedimethanol; diols having a cyclic ether structure such as isosorbide; diols having a fluorene structure; and diols having a bisphenol derivative structure.
[0128] Among these, butanediol, neopentyl glycol, polytetramethylene ether glycol, diols having a fluorene structure, and diols having a bisphenol derivative structure are preferred from the viewpoint of polyester solubility and compatibility with polyimide.
[0129] A diol having a fluorene structure is one that has a fluorene skeleton between two hydroxyl groups and is represented by the following general formula (3).
[0130] [ka]
[0131] In general formula (3), Ar1 and Ar2 are aromatic hydrocarbon rings. 1a and R 1b Each of these is independently an alkyl group or phenyl group having 1 to 10 carbon atoms, and n1 and n2 are independently integers of 0 or greater. 2a and R 2b Each of these is independently an alkyl group or phenyl group having 1 to 10 carbon atoms, and n1 and n2 are independently integers from 0 to 4. 3a and R 3b R is an alkylene group, 5a and R 5b p1 and p2 are independent non-negative integers. q1 and q2 are 1.
[0132] Specific examples of diols represented by general formula (3) include 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene, 9,9-bis[4-(2-hydroxypropoxy)phenyl]fluorene, 9,9-bis[4-[2-(2-hydroxyethoxy)ethoxy]phenyl]-9H-fluorene, 2,2'-[(9H-fluorene-9,9-diyl)bis(naphthalene-6,2-diyloxy)]diethanol, 9,9-bis[4-(2-hydroxyethoxy)-3-phenylphenyl]fluorene, 9,9-bis[4-(2-hydroxypropoxy)-3-phenylphenyl]fluorene, and 9,9-bis{4-[2-(2-hydroxyethoxy)ethoxy]-3-phenylphenyl}fluorene. Among these, 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene, 9,9-bis[4-(2-hydroxypropoxy)phenyl]fluorene, and 9,9-bis[4-(2-hydroxyethoxy)-3-phenylphenyl]fluorene are preferred from the viewpoint of improving heat resistance.
[0133] Diols having a bisphenol derivative structure are those in which an alkylene oxide is added to the two phenolic hydroxyl groups of bisphenol (bisphenol alkylene oxide adducts), with ethylene oxide (EO) adducts and propylene oxide (PO) adducts of bisphenol being preferred. Note that the diols having the fluorene structure of general formula (3) above include diols having a bisphenol derivative structure, but diols having a fluorene skeleton are treated as diols having a fluorene structure, even if they have a bisphenol derivative structure.
[0134] Examples of bisphenols that do not have a fluorene skeleton include 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), 1,1-bis(4-hydroxyphenyl)-1-phenylethane (bisphenol AP), 2,2-bis(4-hydroxyphenyl)butane (bisphenol B), bis(4-hydroxyphenyl)diphenylmethane (bisphenol BP), 2,2-bis(3-methyl-4-hydroxyphenyl)propane (bisphenol C), 1,1-bis(4-hydroxyphenyl)ethane (bisphenol E), bis(4-hydroxyphenyl)methane (bisphenol F), and 2,2-bis(4-hydroxy-3-isopropyl Examples include bis(phenyl)propane (bisphenol G), 1,3-bis(2-(4-hydroxyphenyl)-2-propyl)benzene (bisphenol M), bis(4-hydroxyphenyl)sulfone (bisphenol S), 1,4-bis(2-(4-hydroxyphenyl)-2-propyl)benzene (bisphenol P), 5,5'-(1-methylethylidene)-bis[1,1'(bisphenyl)-2-ol]propane (bisphenol PH), 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane (bisphenol TMC), and 1,1-bis(4-hydroxyphenyl)cyclohexane (bisphenol Z).
[0135] Among bisphenol alkylene oxide adducts, ethylene oxide adducts of bisphenol A, ethylene oxide adducts of bisphenol S, and ethylene oxide adducts of bisphenol Z are preferred from the viewpoint of polyester solubility.
[0136] Polyester may contain diols other than the specified diols mentioned above as diol components. An example of a diol other than the specified diol is ethylene glycol. When the specified diol and ethylene glycol are used together, from the viewpoint of compatibility between polyester and polyimide, the ratio of the specified diol to ethylene glycol is preferably 90:10 to 10:90 in molar ratio, and may also be 80:20 to 20:80, or 60:40 to 40:60. In other words, the amount of the specified diol relative to the total amount of diol components is preferably 10 mol% or more, and may be 20 mol% or more, or 40 mol% or more.
[0137] (Dicarboxylic acid) The dicarboxylic acid component of the polyester is not particularly limited, and various aromatic and aliphatic dicarboxylic acids can be used. Aliphatic and aromatic dicarboxylic acids may be used in combination as the dicarboxylic acid.
[0138] Examples of aromatic dicarboxylic acids include terephthalic acid, isophthalic acid, orthophthalic acid, naphthalenedicarboxylic acid, and biphenyldicarboxylic acid. Furthermore, dicarboxylic acids having a fluorene structure, such as 9,9-bis(carboxymethyl)fluorene and 9,9-bis(2-carboxyethyl)fluorene, can also be cited as examples of aromatic dicarboxylic acids.
[0139] From the viewpoint of improving the solubility and mechanical strength of polyester, terephthalic acid and isophthalic acid are preferred. Terephthalic acid and isophthalic acid may be used individually or in combination. When terephthalic acid and isophthalic acid are used in combination, from the viewpoint of polyester solubility, the molar ratio of terephthalic acid to isophthalic acid is preferably 90:10 to 10:90, and may also be 25:75 to 75:25 or 60:40 to 40:60. From the viewpoint of polyester solubility and mechanical strength, the total amount of terephthalic acid and isophthalic acid relative to the total amount of the dicarboxylic acid component of polyester is preferably 30 mol% or more, more preferably 40 mol% or more, even more preferably 60 mol% or more, and may also be 80 mol% or more.
[0140] Examples of aliphatic dicarboxylic acids include oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanediic acid, dodecanediic acid, fumaric acid, maleic acid, itaconic acid, citraconic acid, 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, and tetrahydrophthalic acid.
[0141] The inclusion of an aliphatic dicarboxylic acid as the dicarboxylic acid component of the polyester may improve the compatibility between the polyester and polyimide. From the viewpoint of improving compatibility with polyimide, aliphatic dicarboxylic acids with 6 to 12 carbon atoms, particularly 6 to 10 carbon atoms, are preferred, and among these, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid are preferred because they can also contribute to improving the solubility of the polyester.
[0142] (Other ingredients) As monomer components constituting the polyester, monomers other than diols and dicarboxylic acids may be used, as long as they do not impair the effects of the present invention. Monomers other than diols and dicarboxylic acids include polyols having 3 or more hydroxyl groups (e.g., trimethylolpropane, glycerin), monoalcohols (e.g., octyl alcohol, decyl alcohol, lauryl alcohol, myristyl alcohol, cetyl alcohol, stearyl alcohol, 2-phenoxyethanol), polycarboxylic acids having 3 or more carboxyl groups (e.g., 1,3,4-benzenetricarboxylic acid, 1,2,4,5-benzenetetracarboxylic acid, pyromellitic acid, trimellitic acid, tetrahydrophthalic acid), monocarboxylic acids (e.g., lauric acid, myristic acid, palmitic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, benzoic acid, p-tert-butylbenzoic acid, cyclohexanoic acid), and hydroxycarboxylic acids (e.g. Examples include compounds having one or more hydroxyl groups and / or one or more carboxyl groups, such as lactic acid, glycolic acid, 2-hydroxybutyric acid, 3-hydroxybutyric acid, 4-hydroxybutyric acid, 2-hydroxyisobutyric acid, 2-hydroxy-2-methylbutyric acid, 2-hydroxyvaleric acid, 3-hydroxyvaleric acid, 4-hydroxyvaleric acid, 5-hydroxyvaleric acid, 6-hydroxycaproic acid, 10-hydroxystearic acid, 4-hydroxyphenylstearic acid, 4-(β-hydroxy)ethoxybenzoic acid), lactones (e.g., β-propiolactone, β-butyrolactone, γ-butyrolactone, δ-valerolactone, ε-caprolactone), and oxiranes (e.g., ethylene oxide), as well as compounds that generate one or more hydroxyl groups and / or one or more carboxyl groups by hydrolysis.
[0143] The polymerization method for polyester is not particularly limited, and various known methods can be employed, such as transesterification reactions, direct esterification to obtain oligomers, followed by melt polymerization or further solid-phase polymerization. In the polymerization of polyester, dicarboxylic acid derivatives such as acid anhydrides may be used as the dicarboxylic acid component.
[0144] From the viewpoint of heat resistance and moldability of the resin composition and molded article, the glass transition temperature (Tg) of polyester is preferably -25 to 200°C, more preferably 15 to 180°C, even more preferably 40 to 150°C, and may be around 60 to 130°C.
[0145] Commercially available polyester resins may be used as the polyester. Examples of commercially available polyester resins containing a diol having a fluorene structure as the diol component include OKP4HT (manufactured by Osaka Gas Chemical, Mw: 38,000, Tg: 142℃) and OKP4 (manufactured by Osaka Gas Chemical, Mw: 40,000, Tg: 121℃). Examples of commercially available polyester resins containing a diol having a bisphenol derivative structure as the diol component include Elytel UE3600 (manufactured by Unitika, Mw: 60,000, Tg: 75℃), Elytel UE3690 (manufactured by Unitika, Mw: 46,000, Tg: 90℃), Elytel UE9100 (manufactured by Unitika, Mw: 77,000, Tg: 19℃), and Byron 290 (manufactured by Toyobo, Mw: 61,000, Tg: 72℃).
[0146] Examples of commercially available polyester resins containing specific diols other than those listed above as diol components include: Elitel UE3200G (manufactured by Unitika, Mw: 43,000, Tg: 65℃), Elitel UE3210 (manufactured by Unitika, Mw: 62,000, Tg: 45℃), Elitel UE3240 (manufactured by Unitika, Mw: 50,000, Tg: 40℃), Elitel UE3500 (manufactured by Unitika, Mw: 83,000, Tg: 15℃), and Elitel UE3 Examples include Unitika 510 (Mw: 63,000, Tg: -25℃), Elitel UE9200 (Unitika, Mw: 39,000, Tg: 65℃), Elitel UE9800 (Unitika, Mw: 40,000, Tg: 85℃), Byron 200 (Toyobo, Mw: 42,000, Tg: 67℃), Byron 240 (Toyobo, Mw: 35,000, Tg: 60℃), and Byron 600 (Toyobo, Mw: 38,000, Tg: 47℃).
[0147] <Preparation of resin composition> A resin composition is prepared by mixing the above-mentioned polyimide with a transparent resin other than polyimide. Polyimides generally do not show compatibility with other polymers, but as mentioned above, polyimides containing a specific diamine as a diamine component show compatibility with transparent resins other than solvent-soluble polyimides.
[0148] To determine whether a specific polyimide is compatible with a transparent resin other than that specific polyimide, a 10 μm thick film containing both the polyimide and the other transparent resin is prepared and checked. If the film is transparent and the haze is 10% or less, the polyimide and the other transparent resin are judged to be compatible. If the film's haze exceeds 10%, the polyimide and the other transparent resin are judged to be incompatible.
[0149] The ratio of polyimide to other transparent resins in the resin composition is not particularly limited. The composition ratio (by weight) of polyimide to other transparent resins may be 2:98 to 98:2, 10:90 to 90:10, 25:75 to 75:25, or 40:60 to 60:40. A higher proportion of polyimide tends to result in higher mechanical strength of molded articles such as films. A higher proportion of other transparent resins tends to result in less coloration and higher transparency of molded articles such as films.
[0150] In order to fully realize the effect of improving transparency by mixing polyimide with other transparent resins, the ratio of the non-polyimide transparent resin to the total of polyimide and other transparent resins is preferably 10% by weight or more, and may be 15% by weight or more, 20% by weight or more, 25% by weight or more, 30% by weight or more, 35% by weight or more, 40% by weight or more, 45% by weight or more, or 50% by weight or more.
[0151] The resin composition may simply be a mixture of polyimide precipitated as a solid component and a transparent resin other than polyimide, or it may be a mixture of polyimide and a transparent resin other than polyimide. Alternatively, when precipitating the polyimide resin by mixing a polyimide solution with a poor solvent, a transparent resin other than polyimide may be mixed into the solution, and the resin composition of polyimide and the transparent resin other than polyimide may be precipitated as a solid (powder).
[0152] The resin composition may be a mixed solution containing polyimide and a transparent resin other than polyimide. The method of mixing the resins is not particularly limited; they may be mixed in a solid state or mixed in a liquid state to form a mixed solution. A polyimide solution and a solution of the transparent resin other than polyimide may be prepared separately, and the two may be mixed to prepare a mixed solution of polyimide and the transparent resin other than polyimide.
[0153] The solvent for a solution containing polyimide and other transparent resins is not particularly limited as long as it is soluble in both polyimide and other transparent resins. Examples of solvents include amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone; ether solvents such as tetrahydrofuran and 1,4-dioxane; ketone solvents such as acetone, methyl ethyl ketone, methyl propyl ketone, methyl isopropyl ketone, methyl isobutyl ketone, diethyl ketone, cyclopentanone, cyclohexanone, and methylcyclohexanone; and alkyl halogenated solvents such as chloroform, 1,2-dichloroethane, 1,1,2,2-tetrachloroethane, chlorobenzene, dichlorobenzene, and dichloromethane.
[0154] Generally, polyimides have low solubility in solvents and often dissolve only in highly polar solvents. Therefore, from the viewpoint of polyimide solubility and compatibility with other transparent resins in solution, amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone are preferred. On the other hand, from the viewpoint of solvent removal when producing molded articles such as films, low-boiling non-amide solvents are preferred. Ketone solvents and alkyl halogen solvents are preferred because they have excellent solubility in both polyimides and other transparent resins, and their low boiling point makes it easy to remove residual solvent during film production.
[0155] The resin composition may contain organic or inorganic low-molecular-weight compounds, high-molecular-weight compounds (e.g., epoxy resins), etc. The resin composition may also contain flame retardants, ultraviolet absorbers (UVA), crosslinking agents, dyes, pigments, surfactants, leveling agents, plasticizers, fine particles, sensitizers, etc. The fine particles may include organic fine particles such as polystyrene and polytetrafluoroethylene, and inorganic fine particles such as colloidal silica, carbon, and layered silicates, and may have a porous or hollow structure. The fiber reinforcing material may include carbon fibers, glass fibers, aramid fibers, etc.
[0156] [Molded articles and films] The above composition can be used to form various molded articles. Molding methods include injection molding, transfer molding, press molding, blow molding, inflation molding, calendering, and melt extrusion. Resin compositions containing polyimide and transparent resins other than polyimide tend to have a lower melt viscosity than polyimide alone and exhibit excellent moldability in injection molding, transfer molding, press molding, and melt extrusion.
[0157] Furthermore, solutions of resin compositions containing polyimide and other transparent resins tend to have lower solution viscosity compared to solutions of polyimide alone at the same solid content concentration. Therefore, they offer superior handling advantages, such as easier transport of the solution, high coating properties, and are advantageous in reducing film thickness variations.
[0158] In the present invention, the molded article is a film, particularly an optical film with excellent transparency. The film can be molded by either a melting method or a solution method, but the solution method is preferred from the viewpoint of producing a film with excellent transparency and uniformity. In the solution method, a film is obtained by coating a solution containing the above-mentioned polyimide and a transparent resin other than polyimide onto a support and drying off the solvent.
[0159] As a method for applying the resin solution onto the support, known methods using bar coaters, comma coaters, etc., can be applied. As the support, glass substrates, metal substrates such as SUS, metal drums, metal belts, plastic films, etc., can be used. From the viewpoint of improving productivity, it is preferable to use an endless support such as a metal drum or metal belt, or a long plastic film, as the support and manufacture the film by roll-to-roll. When using a plastic film as the support, a material that does not dissolve in the film-forming doping solvent should be appropriately selected.
[0160] Heating is preferable when drying the solvent. The heating temperature is not particularly limited as long as it can remove the solvent and suppress discoloration of the resulting optical film, and can be appropriately set between room temperature and approximately 250°C, with 50°C to 220°C being preferred. The heating temperature may be increased in stages. To improve the efficiency of solvent removal, the resin film may be peeled from the support and dried after a certain degree of drying has progressed. Heating may be performed under reduced pressure to promote solvent removal.
[0161] Resin compositions containing polyimide and other transparent resins have a lower glass transition temperature compared to polyimide alone, due to the compatibility of the polyimide and other transparent resins. This allows for molding and processing at lower temperatures and reduces the coloration of molded products such as films.
[0162] The optical film of the present invention is an optical film comprising a polyimide having a structure derived from a diamine and a structure derived from a tetracarboxylic dianhydride, and a transparent resin other than a polyimide, The aforementioned diamine is CF3-O-,-(CF2O) n -, -O-(CF2-CF2-O) n - comprises a diamine having one or more structures selected from any of the following (where n is an integer from 1 to 20), An optical film can be easily manufactured by biaxially stretching a film in which the ratio of diamine-derived structures having a CF3- group directly attached to an aromatic ring or a -C(CF3)2- group directly attached to an aromatic ring to the total amount of diamine-derived structures of the polyimide is less than 0.5 mol%, and the ratio of tetracarboxylic dianhydride-derived structures having a CF3- group directly attached to an aromatic ring or a -C(CF3)2- group directly attached to an aromatic ring to the total amount of tetracarboxylic dianhydride-derived structures is less than 0.5 mol%, thereby achieving an in-plane birefringence ΔN of less than 0.006 and a bending resistance of 100,000 or more cycles when repeatedly bent at a bending radius of 1.0 mm and a speed of 1 cycle per second.
[0163] Optical films containing polyimide and other transparent resins may have low mechanical strength, but this can be improved by stretching the film in at least one direction. When a film is stretched, the polymer chains orient in the stretching direction, which improves the in-plane strength of the film and tends to suppress the occurrence of cracks and fissures. In particular, in compatible systems of polyimide and other transparent resins, the tensile modulus in the stretching direction increases, and consequently, the flexibility tends to improve.
[0164] For example, optical films used as cover films or substrate materials for foldable displays require high mechanical strength in the direction perpendicular to the bending axis because they are repeatedly bent along the bending axis at the same point. Therefore, by arranging the film so that its stretching direction is perpendicular to the bending axis, cracks and breaks are less likely to occur at the bending point even after repeated bending, providing a device with high bending resistance.
[0165] The optical film of the present invention preferably has a bending resistance of 100,000 or more cycles when subjected to repeated bending tests at a bending radius of 1.0 mm and a speed of once per second, more preferably 150,000 or more cycles, and even more preferably 200,000 or more cycles. (However, the repeated bending tests were measured with the film positioned so that the stretching direction of the film was perpendicular to the bending axis.) For optical films made by mixing polyimide and transparent resins other than polyimide, it is preferable that the bending resistance of 100,000 or more cycles when subjected to repeated bending tests at a bending radius of 1.0 mm and a speed of once per second, when a film with a thickness of 50 μm or more is produced.
[0166] The stretching method for optical films is not particularly limited. Various stretching methods can be used, such as free-end stretching, fixed-end stretching, free-end shrinking, and fixed-end shrinking. Among these, free-end stretching, represented by a method in which the film is stretched in the transport direction by the difference in peripheral speed of the nip rolls before and after the film (so-called longitudinal stretching), or fixed-end stretching, represented by a method in which the film is stretched in a direction perpendicular to the transport direction using a tenter clip device (so-called transverse stretching), is preferable from the viewpoint of orienting the molecules in the film in one direction.
[0167] The stretching conditions for optical films are not particularly limited. For example, the stretching temperature is approximately ±40°C of the film's glass transition temperature and may be around 120-300°C, 150-250°C, or 180-230°C. The stretching ratio is approximately 1-200%, and may be 5-150%, 10-120%, or 20-100%. A stretching temperature below 260°C is preferable because it tends to result in a smaller YI (Yield Integrity). A larger stretching ratio tends to result in a larger tensile modulus in the stretching direction. On the other hand, if the stretching ratio is excessively large, the mechanical strength in the direction perpendicular to the stretching direction tends to decrease, which may reduce the handling properties of the film.
[0168] From the viewpoint of increasing strength in any direction within the plane, the film may be biaxially stretched. Biaxial stretching may be sequential biaxial stretching, in which longitudinal stretching is performed followed by transverse stretching, or it may be simultaneous biaxial stretching, in which longitudinal and transverse stretching are performed at the same time. In biaxial stretching, the stretching ratio in one direction and the stretching ratio in the direction perpendicular to it may be the same or different. If there is a difference in the stretching ratio, the mechanical strength tends to be relatively higher in the direction with the larger stretching ratio. When using a biaxially oriented film with anisotropic stretching ratio in a foldable device, it is preferable to position the direction with the larger stretching ratio perpendicular to the folding axis.
[0169] From the viewpoint of heat resistance, it is preferable that the glass transition temperature of the optical film be 110°C or higher, and it may be 115°C or higher or 120°C or higher. Furthermore, from the viewpoint of preventing excessive tension from being applied to the film when stretching it, it is preferable that the glass transition temperature of the optical film be less than 260°C, and it may be less than 250°C, less than 240°C, less than 230°C or less than 220°C.
[0170] The thickness of the optical film is not particularly limited and can be set appropriately depending on the application. For example, the thickness of the optical film is 5 to 300 μm. From the viewpoint of achieving both self-supporting properties and flexibility, and a highly transparent film, the thickness of the optical film is preferably 10 μm to 200 μm, but may also be 30 μm to 150 μm, 40 μm to 100 μm, or 50 μm to 80 μm. For optical film used as a cover film for displays, a thickness of 10 μm or more is preferred. When stretching the film, it is preferable that the thickness after stretching is within the above range.
[0171] The haze of the optical film is not particularly limited, but is preferably 10% or less, more preferably 5% or less, even more preferably 4% or less, and may be 3.5% or less, 3% or less, 2% or less, or 1% or less. As described above, polyimide and transparent resins other than polyimide are compatible, so a film with low haze and high transparency can be obtained. The resin composition obtained by mixing polyimide and transparent resins other than polyimide preferably has a haze of 10% or less when a film with a thickness of 10 μm is made.
[0172] The total light transmittance of the optical film is not particularly limited, but is preferably 85% or higher, more preferably 86% or higher, even more preferably 87% or higher, particularly preferably 88% or higher, and may be 89% or higher or 90% or higher. The resin composition obtained by mixing polyimide and a transparent resin other than polyimide preferably has a total light transmittance of 85% or higher when a film with a thickness of 10 μm is produced.
[0173] The yellowness (YI) of the optical film is not particularly limited, but is preferably 20.0 or less, more preferably 10.0 or less, even more preferably 5.0 or less, and may also be 4.0 or less, 3.0 or less, 2.0 or less, 1.0 or less, or 0.0 or less. The resin composition obtained by mixing polyimide and a transparent resin other than polyimide preferably has a yellowness of 20.0 or less when a film with a thickness of 10 μm is produced. As described above, by mixing polyimide and a transparent resin other than polyimide, a film with less coloration and a lower YI can be obtained compared to when polyimide is used alone.
[0174] The tensile modulus of the optical film is not particularly limited, but from the viewpoint of making the film less prone to tearing, it is preferable that the modulus of elasticity E1 in the first direction, where the elastic modulus is maximum in the plane, and the modulus of elasticity E2 in the second direction, which is orthogonal to the first direction in the plane, satisfy 100 × (E1 - E2) / E2 < 5.0. From the viewpoint of the strength of the optical film, the tensile modulus of the film at room temperature is preferably 2.0 GPa or higher, more preferably 3.0 GPa or higher, and even more preferably 4.0 GPa or higher.
[0175] The pencil hardness of the optical film is not particularly limited, but is preferably 6B or higher, preferably 4B or higher, and may be 2B or higher, F or higher, or 2H or higher. In a compatible system of polyimide and a transparent resin other than polyimide, the pencil hardness does not decrease easily even if the proportion of the transparent resin other than polyimide is increased. Therefore, it is possible to provide a film with less coloration and excellent transparency without significantly reducing the excellent mechanical strength characteristic of polyimide.
[0176] The in-plane birefringence ΔN of the optical film is preferably less than 0.006, more preferably less than 0.005, even more preferably less than 0.002, and particularly preferably less than 0.0015. The birefringence ΔP in the thickness direction of the optical film is not particularly limited, but is preferably less than 0.020, more preferably less than 0.015, even more preferably less than 0.010, and particularly preferably less than 0.006.
[0177] The in-plane birefringence ΔN is the difference between the refractive index nx in the direction of maximum in-plane refractive index (slow axis direction) and the refractive index ny in the direction perpendicular to the slow axis in-plane (fast axis direction). The frontal retardation of the film is obtained by multiplying the in-plane birefringence ΔN by the thickness of the film. The birefringence ΔP in the thickness direction is the difference between the average of the refractive index nx in the slow axis direction and the refractive index ny in the fast axis direction and the refractive index nz in the thickness direction: (nx+ny) / 2-nz. The thickness phase difference of the film is obtained by multiplying the birefringence ΔP in the thickness direction by the thickness of the film. The smaller the birefringence ΔN and ΔP of the film, the higher the visibility tends to be when applied to a display.
[0178] Optical films formed from resin compositions containing polyimide and other transparent resins are suitable for use as display materials due to their low coloration and high transparency. In particular, films with high mechanical strength can be applied to surface components such as cover windows of displays. Optical films formed from the above-mentioned resin compositions containing polyimide and other transparent resins can achieve both high transparency and high mechanical properties by stretching. For practical use, the film of the present invention may be provided with an antistatic layer, an easy-adhesion layer, a hard coat layer, an anti-reflective layer, etc., on its surface. [Examples]
[0179] The embodiments of the present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following embodiments.
[0180] [Preparation of polyimides] <Preparation and imidation of polyamic acids> Dimethylformamide (hereinafter referred to as DMF) was placed in a separable flask and stirred under a nitrogen atmosphere. Diamine and tetracarboxylic dianhydride were then added in the ratios (mol%) shown in Table 1, followed by the addition of acetic acid. The mixture was then stirred under a nitrogen atmosphere for 5 to 10 hours to obtain a polyamic acid solution with a solid content of 13% by weight. Pyridine was added to the obtained polyamic acid solution and dispersed completely. Then, acetic anhydride was added and the mixture was stirred at 90°C for 3 hours to carry out imidation.
[0181] <Isolation of Polyimides> After cooling the imidized solution to room temperature, 2-propyl alcohol (indicated as IPA) was added dropwise while stirring the solution to precipitate the polyimide resin. Further IPA was added, and after stirring for about 30 minutes, suction filtration was performed using a Kiriyama funnel. The obtained solid was washed with IPA and then dried in a vacuum oven set to 120°C for 12 hours to obtain polyimide.
[0182] [Preparation of resin compositions (solutions) and fabrication of optical films] <Preparation of resin composition (solution)> The above polyimide (PI) and a commercially available transparent resin other than polyimide (hereinafter referred to as "general-purpose resin") were added to methylene chloride in the weight ratios shown in Table 1 to prepare a resin solution with a solid content of 10% by weight. For Examples 1-4, Reference Example 1, and Comparative Example 1, LA-31G (manufactured by ADEKA Corporation) at 5.5 wt% relative to the total amount of resin was added as UVA, and ET 4B403 (manufactured by Dainichi Seika Kogyo Co., Ltd.) at 0.02 wt% relative to the total amount of resin was added as a pigment, and the mixture was completely dissolved. The general-purpose resins are as follows.
[0183] Acrylic: G1000 (manufactured by Kuraray Co., Ltd., weight-average molecular weight 98,000, Tg: 130℃) PEs: Elitel UE3600 (manufactured by Unitika Ltd., weight-average molecular weight 60,000, Tg: 75℃)
[0184] The weight-average molecular weight of general-purpose resins was measured using a gel permeation chromatography system (equivalent to HLC-8220GPC) manufactured by Tosoh Corporation under the following conditions. Developing solvent: LiBr (10 mM) DMF solution Sample concentration: 0.15% by weight Flow rate: 0.6mL / min Column configuration: From upstream, TSK guard column Super AW-H, TSK gel AWM―H, TSK gel AWM―H Column temperature: 40℃ Detection conditions: RI, UV Molecular weight standard: Polystyrene (manufactured by Tosoh Corporation)
[0185] <Fabrication of optical films> In Examples 1-6 and Reference Example 1, the above resin solution was coated onto an alkali-free glass plate and heated and dried in an air atmosphere at 40°C, 60°C, 90°C, 120°C, 150°C, and 200°C for 15 minutes each. After drying, the glass was peeled off to produce a film with a thickness of 100-130 μm. In Comparative Examples 1-3, optical films were prepared with a thickness of 50 μm. The optical films were coated in the MD direction and in the TD direction.
[0186] [Stretching of optical films] The above optical film, after drying, was stretched at the stretching temperature and stretching ratio listed in Table 1 to obtain an optical film with a thickness of 50 μm. A stretching ratio of 50% means stretching the film until it is 1.50 times the length of the film before stretching. In Examples 1, 2, 5, and 6, simultaneous biaxial stretching was performed, stretching in the MD and TD directions simultaneously. In Examples 3 and 4, sequential biaxial stretching was performed, with free-end stretching (longitudinal stretching) in the MD direction followed by fixed-end stretching (transverse stretching) in the TD direction. In Reference Example 1, only fixed-end stretching (transverse stretching) in the TD direction was performed.
[0187] [evaluation] <Glass transition temperature (Tg)> Test specimens were prepared by cutting strips measuring 25 mm in length and 5 mm in width from the optical films obtained in the Examples and Reference Examples before stretching, and from the optical films obtained in the Comparative Examples. The storage modulus E' and loss modulus E'' were measured using a dynamic viscoelasticity analyzer (UBM, Rheogel-E4000) in tensile mode, with an initial chuck distance of 15 mm, a frequency of 10 Hz, and a heating rate of 10 °C / min, while heating from 30 °C to 300 °C. E'' / E' (=tanδ) was plotted against temperature, and the temperature at which it reached its maximum was defined as the glass transition temperature (Tg).
[0188] <Module of elasticity E1, E2> The films obtained in the Examples, Comparative Examples, and Reference Examples were cut into strips 10 mm wide so that the MD direction was the longitudinal direction, and after being left to stand for 1 day at 23°C / 55%RH to conditioned the humidity, the tensile modulus in the MD direction was measured under the following conditions using a Shimadzu Corporation tensile testing machine "AUTOGRAPH AGS-X". Distance between gripping parts: 100mm Tensile speed: 20.0 mm / min Measurement temperature: 23℃ For the TD direction as well, the material was cut into strips 10 mm wide so that the TD direction was the longitudinal direction, and the tensile modulus was measured using the same method as for the MD direction, and this was determined as the modulus of elasticity in the TD direction. These moduli of elasticity in the MD direction and the moduli of elasticity in the TD direction were compared, and the larger one was designated as E1, and the smaller one as E2.
[0189] <Difference in elastic modulus R> The elastic modulus in the MD direction and the elastic modulus in the TD direction were calculated using 100 × (E1 - E2) / E2, and the resulting value was defined as the difference in elastic modulus R (%).
[0190] <Haze and total light transmittance> Haze and total light transmittance (TT:%) were measured using a Suga Test Instruments HZ-V3 haze meter in accordance with JIS K7136 and JIS K7361-1. A D65 light source was used for the measurements.
[0191] <Yellowness> The yellowness (YI) was measured according to JIS K7373 using a spectrophotometer "SC-P" manufactured by Suga Test Instruments.
[0192] <Flexural resistance> The film obtained in the example was cut into strips measuring 120 mm in length and 20 mm in width, with the MD direction as the longitudinal direction, to prepare test specimens. Using a Yuasa System Equipment U-shaped bending durability tester DMLHB, repeated bending tests were performed at 23°C / 55%RH with a bending radius of 1.0 mm and a speed of 1 time / second, with the TD direction as the bending axis. The presence or absence of cracks or fractures was checked every 10,000 cycles. The maximum number of cycles without cracks or fractures after repeated bending was defined as the bending resistance in the MD direction. The same repeated bending test was performed in the TD direction, and the maximum number of cycles without cracks or fractures after repeated bending was defined as the bending resistance in the TD direction. The films obtained in the comparative example and reference example were also measured for similar bending resistance.
[0193] <Birefringence> Using the KOBRA phase difference measuring device manufactured by Oji Instruments, the phase difference at a wavelength of 589 nm was measured using the parallel nicol rotation method, and the front phase difference R0 was measured. The birefringence ΔN was defined as the front phase difference R0 divided by the film thickness.
[0194] In Table 1, the compounds are listed using the following abbreviations. <Diamine> TFMOB: 2,2'-Bis(trifluoromethoxy)benzidine
[0195] <Tetracarboxylic acid dianhydride> BPAF: 9,9-Bis(3,4-dicarboxyphenyl)fluorenedioxide anhydride BPADA: 4,4'-(4,4'-isopropylidene diphenoxy)diphthalic anhydride CBDA: 1,2,3,4-cyclobutanetetracarboxylic dianhydride
[0196] [Table 1]
[0197] The optical films shown in Examples 1-6 had a birefringence ΔN of less than 0.006, a difference between the elastic modulus E1 and E2 (R(%)) of less than 5%, and a bending resistance of 100,000 cycles or more in both the MD and TD directions. On the other hand, the unstretched optical films shown in Comparative Examples 1-3 had a birefringence ΔN of less than 0.006 and a difference between the elastic modulus E1 and E2 of less than 5%, but a bending resistance of less than 100,000 cycles. In Reference Example 1, the bending resistance in the TD direction was 100,000 cycles or more, but the bending resistance in the MD direction was less than 100,000 cycles, and the birefringence ΔN was greater than 0.006.
Claims
1. An optical film comprising a polyimide having a structure derived from a diamine and a structure derived from a tetracarboxylic dianhydride, and a transparent resin other than a polyimide, The diamine is CF 3 -O-, -(CF 2 -O) n -, -O-(CF 2 -CF 2 -O) n - comprises a diamine having one or more structures selected from any of the above (where n is an integer from 1 to 20), In said polyimide, with respect to the total amount of diamine-derived structures, CF directly bonded to an aromatic ring 3 - group or -C(CF directly bonded to an aromatic ring 3 ) 2 - containing diamine-derived structure accounts for less than 0.5 mol%, and with respect to the total amount of tetracarboxylic dianhydride-derived structures, CF directly bonded to an aromatic ring 3 - group or -C(CF directly bonded to an aromatic ring 3 ) 2 - containing tetracarboxylic dianhydride-derived structure accounts for less than 0.5 mol%, The optical film is characterized in that its in-plane birefringence ΔN is less than 0.006, and its bending resistance is 100,000 times or more when repeatedly bent at a bending radius of 1.0 mm at a speed of once per second.
2. The CF 3 -O-, -(CF 2 -O) n -, -O-(CF 2 -CF 2 -O) n The optical film according to claim 1, characterized in that one or more diamines having structures selected from any of the following (where n is an integer from 1 to 20) are selected from 2,2'-bis(trifluoromethoxy)benzidine, 3,3'-bis(trifluoromethoxy)benzidine, and 2,3'-bis(trifluoromethoxy)benzidine.
3. The optical film according to claim 1, characterized in that the transparent resin other than the polyimide is selected from either an acrylic resin or a polyester.
4. The optical film according to claim 1, characterized in that its glass transition temperature is 110°C or higher and less than 260°C.
5. The optical film according to claim 1, comprising the polyimide and a transparent resin other than the polyimide in a weight ratio in the range of 2:98 to 98:
2.
6. The optical film according to claim 1, characterized in that the elastic modulus E1 in the first direction, which has the maximum elastic modulus in the plane, and the elastic modulus E2 in the second direction, which is orthogonal to the first direction in the plane, satisfy 100 × (E1 - E2) / E2 < 5.0, and both the elastic modulus E1 in the first direction and the elastic modulus E2 in the second direction are 3.0 GPa or greater.
7. The optical film according to claim 1, wherein the total light transmittance is 85% or more, the haze is 10% or less, and the yellowness is 5 or less.
8. A method for manufacturing an optical film according to any one of claims 1 to 7, characterized by biaxial stretching.
9. A method for manufacturing an optical film according to claim 8, wherein the temperature during stretching is less than 260°C.
Citation Information
Patent Citations
Polyimide film and its manufacturing method
JP6912287B2
Film, production method therefor, and image display device
WO2023100806A1